Replication of plasmid RK2 in vitro by a DNA-membrane complex: evidence for initiation of replication and its coupling to transcription and translation. - Kornacki, J A (1986)
The following results with an in vitro replication system utilizing a plasmid RK2 DNA-membrane complex indicate that the essential trfA-encoded replication protein of RK2 is present and active in the complex. (i) A complex extracted from a conditional replication mutant of RK2, which contains a temperature-sensitive mutation in trfA, displayed extensive DNA synthesis at the permissive temperature but little activity at the restrictive temperature. A control wild-type RK2 complex showed no inhibition of DNA synthesis at the restrictive temperature. (ii) Analysis of plasmid-encoded proteins revealed that the trfA-specified replication protein and other proteins which may be involved in the replication and maintenance of RK2 are located physically in the complex. Semiconservative plasmid DNA replication by the DNA-membrane complex was indicated by density shift experiments; DNA synthesized in the presence of a heavy-density precursor banded primarily in a heavier-density area of a neutral CsCl density gradient and consisted mostly of heavy- and light-density single-stranded DNA as determined by alkaline CsCl density gradient centrifugation. Plasmid RK2 DNA replication by the DNA-membrane complex appears to be coupled to transcription and translation as indicated by the following results: the inhibitory effects of chloramphenicol on both DNA and protein synthesis by the complex; the stimulation of replication by components normally required for protein synthesis (tRNA and all the common amino acids); the synthesis of RNA and protein by the complex; and the synthesis of specific RK2-encoded proteins.